Determination of Aluminium in Rock Samples by Energy Dispersive Fluorescence Spectroscopy - S. Karaaslan, Ipek; Bayrakceken, Fuat (Asian Journal of Chemistry, 2010)
Optical emission spectroscopy and fast imaging of the arc process of aluminium and its alloys were carried out to determine the concentration of the aluminium in the rock samples. Optical measurement allow the establishment of relationships between the spark aspect and the aluminium emission line's intensity. The proposed method has been applied to the determination of aluminium in rock samples with satisfactory results. The simplicity, low cost and easy operation were the main advantages of the present procedure. The proposed method was applied to the simultaneous multielement determination. The results were well within the recommended standard values.